2018
DOI: 10.1111/jcpe.12948
|View full text |Cite
|
Sign up to set email alerts
|

Mucogingival conditions in the natural dentition: Narrative review, case definitions, and diagnostic considerations

Abstract: The clinical impact and the prevalence of conditions like root surface lesions, hypersensitivity, and patient esthetic concern associated with gingival recessions indicate the need to modify the 1999 classification. The new classification includes additional information, such as recession severity, dimension of the gingiva (gingival biotype), presence/absence of caries and non-carious cervical lesions, esthetic concern of the patient, and presence/absence of dentin hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
199
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(215 citation statements)
references
References 64 publications
3
199
0
13
Order By: Relevance
“…This is the first study that has evaluated gingival thickness through the periodontal probe's translucency (thin and adequate biotype) with different vertical facial heights, and these findings support the hypothesis that there is no correlation between facial morphology and gingival thickness on lateral cephalograms [24]. Gingival thickness can be assessed by transgingival probing [38], ultrasonic measurement [39], or through the visibility of the probe [40,41]. Transgingival probing was not used because of the need for local anesthesia, which could induce a local volume increase and discomfort for patients [38].…”
Section: Discussionsupporting
confidence: 67%
“…This is the first study that has evaluated gingival thickness through the periodontal probe's translucency (thin and adequate biotype) with different vertical facial heights, and these findings support the hypothesis that there is no correlation between facial morphology and gingival thickness on lateral cephalograms [24]. Gingival thickness can be assessed by transgingival probing [38], ultrasonic measurement [39], or through the visibility of the probe [40,41]. Transgingival probing was not used because of the need for local anesthesia, which could induce a local volume increase and discomfort for patients [38].…”
Section: Discussionsupporting
confidence: 67%
“…Population studies on the frequency of gingival recession showed a varied level of its prevalence, which was 19% in Swedes, 30% in the population of Poles, and 50% in Germany (Cortellini & Bissada, 2018;Dominiak & Gedrange, 2014;Sulewska et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Scientific rationale for the study: Although predictability of root coverage procedures has been extensively demonstrated for the treatment of single and multiple gingival recessions, outcomes in terms of aesthetic outcomes, satisfaction and patient morbidity are still unclear. (Cairo, Nieri, Cincinelli, Mervelt, & Pagliaro, 2011;Cortellini & Bissada, 2018a…”
Section: Clinical Relevancementioning
confidence: 99%